Badger Robotic Mining Team - Atruktsang, Tashi (Proceedings of the Wisconsin Space Conference, 2017)
This is a paper on the Badger Robotic Mining Team, their organization and the year of work that the students put into their robot and the organization. This paper will cover the background of the project, its importance and how the team spent the year working on their robot in terms of their mechanical side of the project as well as the controls side.